PERSONAL BRANDING JOKOWI DALAM MEMPERTAHANKAN BRAND IMAGE MELALUI VIDEO BLOG YOUTUBE - Mohammad Insan Romadhan (Universitas Lambung Mangkurat, 2018)
ABSTRACT The development of new media that is so rapidly in particular social media at a time when the media makes many overlapping with varying degrees of human life, including use as a branding medium one is personal branding. Jokowi is one of the people leverage social media in particular youtube in branding. The youtube channel of Jokowi was registered on youtube starting on 6 may 2015, per November 2017 already as much as 19 million impressions and uploded around 250 videos. Research using qualitative approach, with the kind of descriptive research. The subject of this research is the youtube channel of Jokowi, its data collection techniques using observation and documentation of data analysis techniques using while Creswell. In this study using a literature review regarding the brand, especially personal branding. The results of his research Personal branding done Jokowi through video blogs on youtube channel can be said to succeed in maintaining brand image that's been built up that he was a President of a simple, close to the people, friendly and built Indonesia.Key words: Personal branding, Youtube, Jokowi